A Group Journey—to Hell and Back. Issue 4 (2nd October 2017) - Sagi Berg, Sharon
ABSTRACT: The process of a therapy group in an inpatient daycare unit 1 became saturated with anger and detachment, ultimately leading to a despairing silence. Based on Ferenczi's concept of Orpha, I will explain the group silence as indicative of deep trauma and dissociative self-states. I propose that the therapist's willingness to "hang in" with his group and be part of a seemingly unbearable enactment enhances the possibility for emergence of hope and restoration of positive communication. It is rare in the literature for authors to expose the pitfalls that they and their group members can fall into, leading to despair, shame, and hopelessness. When working in the complex environment of a mental hospital where every level of staff is stressed, therapists often find themselves without support and consultation. My hope is that my colleagues can learn from my challenges, errors, and lessons, as I have.